Working at home: French MEPs' day-to-day practice of political representation in their district. Issue 1 (2nd January 2018) - Poyet, Corentin
ABSTRACT: In the early 2000s, Simon Hix and his colleagues declared the European Parliament (EP) constitutes a good laboratory to test theories and hypotheses about legislative or party behaviour. However, scholars mainly focused on roll-call votes analysis, allowing them to investigate voting behaviour, coalition formation as well as activities in committees. The author argues that work in parliament should not be investigated without considering constituency work. Surprisingly, despite the institutionalisation of district work, only a few studies have focused on micro-level linkages between members of the European Parliament (MEPs) and citizens. The results show that MEPs are in contact with citizens having matters to do with the European Union (EU) but not directly with their constituents. In the district, MEPs are more experts of the EU than members of the community. By investigating day-to-day contacts between citizens and their MEPs, this paper offers a new perspective on the debate about the democratic deficit of EP and EU institutions.